Structural and ultrastructural characteristics of the yolk syncytial layer in Prochilodus lineatus (Valenciennes, 1836) (Teleostei; Prochilodontidae) - Ninhaus-Silveira, A.; Foresti, F.; de Azevedo, A.; Agostinho, Claudio Angelo [UNESP]; Verissimo-Silveira, R. (Cambridge University Press, 2007)
The yolk syncytial layer (YSL) has been regarded as one of the main obstacles for a successful cryopreservation of fish embryos. The purpose of this study was to identify and characterize the YSL in Prochilodus lineatus, a fish species found in southeastern Brazil and considered a very important fishery resource. Embryos were obtained through artificial breeding by hormonal induction. After fertilization, the eggs were incubated in vertical incubators with a controlled temperature (28 degrees C). Embryos were collected in several periods of development up to hatching and then fixed with 2% glutaralclehyde and 4% paraformaldehyde in 0.1 M sodium phosphate buffer (pH 7.3). Morphological analyses were carried out under either light, transmission or scanning electron microscopy. The formation of the YSL in P. lineatus embryos starts at the end of the cleavage stage (morula), mainly at the margin of the blastoderm, and develops along the embryo finally covering the entire yolk mass (late gastrula) and producing a distinct intermediate zone between the yolk and the endodermal cells. The YSL was characterized by the presence of microvilli on the contact region with the yolk endoderm. A cytoplasmic mass, full of mitochondria, vacuoles, ribosomes, endomembrane nets and euchromatic nuclei, indicated a high metabolic activity. This layer is shown as an interface between the yolk and the embryo cells that, besides sustaining and separating the yolk, acts as a structure that makes it available for the embryo. The structural analyses identified no possible barriers to cryoprotectant penetration.
Keywords: cryopreservation; embryo; morphology; periblast; teleost